2018
DOI: 10.1021/acs.jmedchem.8b01282
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Amphipathic Peptide Hydrogels as Extended-Release System for Opioid Peptides

Abstract: Chronic pain is currently treated with opioids that offer unsatisfactory long-term analgesia and produce serious side effects. There is a clear need for alternative therapies. Herein, peptide-based hydrogels are used as extended-release drug delivery carriers. Two different formulations were developed: the drug is coformulated within the hydrogel; the drug is an integral part of the hydrogelator. Both strategies afford a prolonged and significant antinociception up to 72 h after subcutaneous administration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Whereas specific binding of DALDA and [Dmt 1 ]DALDA to the MOR in the rat brain has been reported previously [ 32 ], with both ligands showing high affinity and selectivity for the MOR, in the present study the first data on binding affinity to the human MOR is reported. Binding to the human MOR was evaluated using in vitro competitive radioligand binding assays with membrane preparations from Chinese hamster ovary cells stably expressing the human MOR (CHO-hMOR cells) and the specific MOR radioligand [ 3 H]DAMGO, according to the published procedures [ 43 ]. All three peptides displayed high capability to inhibit [ 3 H]DAMGO binding to the human MOR in a concentration-dependent manner ( Figure 2 A), with binding affinities (as K i values) in the low nanomolar to subnanomolar range ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas specific binding of DALDA and [Dmt 1 ]DALDA to the MOR in the rat brain has been reported previously [ 32 ], with both ligands showing high affinity and selectivity for the MOR, in the present study the first data on binding affinity to the human MOR is reported. Binding to the human MOR was evaluated using in vitro competitive radioligand binding assays with membrane preparations from Chinese hamster ovary cells stably expressing the human MOR (CHO-hMOR cells) and the specific MOR radioligand [ 3 H]DAMGO, according to the published procedures [ 43 ]. All three peptides displayed high capability to inhibit [ 3 H]DAMGO binding to the human MOR in a concentration-dependent manner ( Figure 2 A), with binding affinities (as K i values) in the low nanomolar to subnanomolar range ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we have compared in vitro functional activities of DALDA, [Dmt 1 ]DALDA and KGOP01 at the human MOR in the guanosine-5′-O-(3-[ 35 S]thio)-triphosphate ([ 35 S]GTPγS) binding assay using membranes from CHO cells stably expressing the human MOR, performed as described [ 43 ]. All tested peptides produced a concentration-dependent increase in the [ 35 S]GTPγS binding with different levels of potencies ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ballet and coworkers developed new peptide‐based hydrogels as extended‐release system for opioids which formed thixotropic injectable hydrogels upon dissolution in aqueous solutions. The efficacy of the hydrogel networks as a controlled drug delivery platform was demonstrated for morphine, showing extended antinociceptive effect up to 72 h after subcutaneous administration in mice . The topical administration of opioids is an effective therapeutic method.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro binding assays were conducted on human opioid receptors stably transfected into CHO cells according to the published procedures 26 . Binding assays were conducted on human opioid receptors stably transfected into CHO cells (CHO-hMOR, CHOhDOR, and CHO-hKOR) according to previously published procedures 26,40 . Cell membranes were prepared as described previously 26 , and stored at − 80 °C until use.…”
Section: Pharmacology Compounds Chemicals and Reagents Corydine (1mentioning
confidence: 99%